An innovative methodology for managing service disruptions on regional rail lines - Botte, Marilisa; Puca, Domenico; Montella, Bruno; D’Acierno, Luca (International Conference “Environmental Engineering”, 2017)
Regional rail transport, albeit a major element in public mobility, is frequently affected by great vulnerability to system failure. Hence it is worth developing suitable procedures to manage rail disruption appropriately. In the particular case of breakdowns, the latter may be managed by means of shunter locomotives or empty rail convoys if the faulty convoy is able to travel in non-autonomous conditions. Obviously, the use of rescue vehicles on the line generates a disturbance with related reductions in service quality. Against this backdrop, this paper has two main aims. First, we investigate the possibility of adopting some unconventional rescue strategies based on the use of operating rail convoys or maintenance vehicles, and propose a methodology, based on a micro-simulation approach, for accurately modelling interactions among all rail system components so as to optimise management in emergency contexts. The second aim is to identify suitable intervention strategies which provide the right balance between the swiftness of rescue operations and the disturbance inflicted upon rail services during failure management. Finally, the method is applied to the ‘Naples-Sorrento’ regional rail line in southern Italy in order to show the utility and feasibility of the suggested approach.